The agitated pediatric patient located in the emergency department: The APPLIED observational study. Issue 3 (20th June 2022) - Manuel, Matthias M.; Feng, Sing‐Yi; Yen, Kenneth; Patel, Faisalmohemed
Abstract: Objectives: Focused research on pediatric agitation is lacking despite being a common mental and behavioral health (MBH) emergency. Prevalence of pediatric agitation remains unknown, and prior reports may have underestimated the rate of restraint use for pediatric agitation. This is the largest study to provide a focused evaluation of the prevalence and predictors of pediatric agitation and restraint use as well as the emergency department (ED) length of stay (LOS) and admission rates for agitated patients. Methods: We reviewed records of patients aged ≤18 years with MBH needs who visited the pediatric ED of a tertiary care hospital during a 3‐year‐period. We identified and ascertained agitated/aggressive patients using documented signs/symptoms, International Classification of Diseases, Tenth Revision codes, and Behavioral Activity Rating Scale scores. We performed descriptive and multivariable analyses using SAS 9.4 (SAS Institute). Results: Of 10, 172 patients with MBH needs, 1408 (13.8%) were agitated/aggressive. Of these (n = 1408), 63.7% were boys, and the mean age was 11.9 years. Among agitated patients, the prevalence of restraint use was 28.7%, with a predominance of pharmacologic restraint with atypical antipsychotics. Non‐Hispanic Blacks were more likely to be agitated (adjusted odd ratio [aOR], 1.8; 95% CI, 1.2–2.7), but not restrained (aOR, 0.8; 95% CI, 0.3–1.8). Predictors of restraint use include history of attention deficit hyperactivity disorder (aOR, 2.2; 95% CI, 1.5–3.3), autism (aOR, 2.9; 95% CI, 1.9–4.5), conduct disorder (aOR, 1.7; 95% CI, 1.2–2.5), psychosis (aOR, 14.3; 95% CI, 2.5–271.8), and substance use/overdose states (aOR, 1.9; CI, 1.2–3.2). Restrained agitated patients had longer ED LOS (8.4 vs 5.0 hours; P  < 0.0001) and higher admission rates (aOR, 2.6; 95% CI, 2.0–3.5). Depression (aOR, 0.4; 95% CI, 0.3–0.5) and suicidality (aOR, 0.2; 95% CI, 0.1–0.3) were protective against agitation and restraint use. Conclusion: Prevalence of acute agitation and restraint use in pediatric EDs may be much higher than previously reported. Predictors of acute agitation and restraint use among MBH patients were consistent with prior reports. Restrained agitated patients had longer ED LOS and higher admission rates.